2018
DOI: 10.1166/asl.2018.10710
|View full text |Cite
|
Sign up to set email alerts
|

Malware Classification Using Ensemble Classifiers

Abstract: Antimalware offers detection mechanism to detect and take appropriate action against malware detected. To evade detection, malware authors had introduced polymorphism to malware. In order to be effectively analyzing and classifying large amount of malware, it is necessary to group and identify them into their corresponding families. Hence, malware classification has appeared as a need in securing our computer systems. Algorithms and classifiers such as k-Nearest Neighbor, Artificial Neural Network, Support Vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Artificial speech detection techniques have witnessed significant evolution, falling into three primary categories: classic machine learning, end-to-end learning, and hybrid methodologies. Classic machine learning entails the manual crafting and extraction of predetermined features from data samples, which are then subject to separate classification modules [4,5]. In contrast, end-to-end learning orchestrates the automatic and joint identification and learning of all data sample features to determine their class labels.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial speech detection techniques have witnessed significant evolution, falling into three primary categories: classic machine learning, end-to-end learning, and hybrid methodologies. Classic machine learning entails the manual crafting and extraction of predetermined features from data samples, which are then subject to separate classification modules [4,5]. In contrast, end-to-end learning orchestrates the automatic and joint identification and learning of all data sample features to determine their class labels.…”
Section: Related Workmentioning
confidence: 99%
“…This approach extracts text-based features from the hexadecimal representation of audio data to create a feature space. Drawing inspiration from previous studies [5,9], which effectively counted opcode occurrences in executable files for malware classification, we adapted this method for artificial speech detection. Leveraging the hexadecimal representation of speech, our study aimed to extract features capable of distinguishing between bonafide and spoofed speech.…”
Section: Feature Engineering Using Data Transformation Approachmentioning
confidence: 99%
“…A work that utilizes features extracted from hexadecimal represented data for classification problems were found in [6], [7]. In the works [6], [7] the occurrences of each opcode in the executable file were counted and used as features to classify malicious software (malware). The approach used by [6], [7] produced high accuracy in malware classification.…”
Section: Hexadecimal Frequenciesmentioning
confidence: 99%
“…In the works [6], [7] the occurrences of each opcode in the executable file were counted and used as features to classify malicious software (malware). The approach used by [6], [7] produced high accuracy in malware classification. The approach was able to achieve good performance because the different classes of malware usually have a higher frequency of certain opcodes.…”
Section: Hexadecimal Frequenciesmentioning
confidence: 99%
“…The application of multiple classifiers in PAD systems also can be found in the literature. In many domains involving machine learning and classification, it has been shown that applying ensemble classifiers may improve the performance of a system [42,79]. Nevertheless, in the field of voice recognition, it has been shown that applying multiple classifiers with the same feature hardly improves the performance of the voice PAD system [15].…”
Section: Classifiersmentioning
confidence: 99%